2017
DOI: 10.4007/annals.2017.185.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Progression-free sets in $\mathbb{Z}_4^n$ are exponentially small

Abstract: Abstract. We show that for integer n ≥ 1, any subset A ⊆ Z n 4 free of three-term arithmetic progressions has size |A| ≤ 4 γn , with an absolute constant γ ≈ 0.926. Background and MotivationIn his influential papers [R52, R53], Roth has shown that if a set A ⊆ {1, 2, . . . , N } does not contain three elements in an arithmetic progression, then |A| = o(N ) and indeed, |A| = O(N/ log log N ) as N grows. Since then, estimating the largest possible size of such a set has become one of the central problems in addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
215
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(217 citation statements)
references
References 14 publications
(1 reference statement)
2
215
0
Order By: Relevance
“…For the homocyclic groups of exponent 4 this result was improved by Sanders, who proved that r 3 (Z 4 n ) = O(4 n /n(log n) ε ) with an absolute constant ε>0. Croot, Lev and Pach [169] further improved Sanders's result. They showed that r 3 (Z 4 n ) = O(3.62 n ).…”
Section: Combinatorial Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…For the homocyclic groups of exponent 4 this result was improved by Sanders, who proved that r 3 (Z 4 n ) = O(4 n /n(log n) ε ) with an absolute constant ε>0. Croot, Lev and Pach [169] further improved Sanders's result. They showed that r 3 (Z 4 n ) = O(3.62 n ).…”
Section: Combinatorial Resultsmentioning
confidence: 60%
“…Starting from Roth, the standard way to obtain quantitative estimates for r 3 (G) involves a combination of the Fourier analysis and the density increment technique. In contrast, in [169] a new variant of the polynomial method is developed and used without resorting to the familiar Fourier analysis-density increment strategy.…”
Section: Combinatorial Resultsmentioning
confidence: 99%
“…As we mentioned at the end of Section 3.1, by recent breakthrough work [23,27], such subsets A ⊂ F n 3 have polynomially small density, |A| < (3 n ) 1−ε for some positive constant ε.…”
Section: Sets Without Arithmetic Progressionsmentioning
confidence: 95%
“…Subsequently, Bateman and Katz [7] improved the bound to |A| ≤ (c/n 1+ε ) · 3 n for some small unspecified constant ε > 0. Very recently, breakthrough works of Croot, Lev and Pach [23] and Ellenberg and Gijswijt [27] improved the bound to c n for c < 3 an absolute constant. Their techniques are quite different; we refer the interested reader to the papers for details.…”
Section: Theorem 32 (Szemerédi)mentioning
confidence: 99%
“…First, Croot, Lev, and Pach obtained an upper bound of this exponential type for subsets of Z n 4 with no 3-term arithmetic progression [12]. Then, barely a week later, Jordan Ellenberg and Dion Gijswijt independently saw how to modify the argument of Croot, Lev, and Pach to give a similar bound for the cap-set problem itself, thereby giving a positive answer to the question above [13].…”
Section: A First Generalization-to Arbitrary Finite Abelian Groupsmentioning
confidence: 99%